Surgical Management in Patients With Pancreatic Cancer: a Queensland Perspective - Wylie, N.; Adib, R.; Barbour, A.; Fawcett, J.; Hill, A.; Lynch, S.; Martin, I.; O'Rourke, T.; Puhalla, H.; Rutherford, L.; Slater, K.; Whiteman, D.; et al. (John Wiley & Sons, 2013)
Background: Little has been published regarding presenting symptoms, investigations and outcomes for patients with pancreatic cancer in Australia. Data from a series of patients undergoing attempted resection in Queensland, Australia, are presented with the aim of assisting development of consistent strategies in disease management.Methods: We reviewed the medical records of 121 patients who underwent attempted surgical resection and who took part in a case-control study between 2007 and 2009. Information relating to symptoms, investigations, surgical procedures and outcomes was captured.Results: The mean age was 63 years and 60% were men. The most common presenting symptoms were jaundice (64%) and pain (63%). Over 80% of patients had multiple imaging investigations or laparoscopy prior to surgery. Seventy-eight patients (64%) had a completed resection and 23% of these had involved margins. The presence of metastases and/or involvement of vessels or adjacent structures precluded resection in the remaining patients. The 1-year survival for patients whose resections were completed was 77% compared with 51% for those whose tumours were notresectable (P = 0.004). There was no 30-day mortality and 68% of patients were alive 1 year after diagnosis. Resections were performed in 11 different hospitals but over 90% of patients underwent their surgery in one of five high-volume centres.Conclusion: The Queensland experience is consistent with that reported internationally. A significant proportion of attempted resections was not completed because preoperative staging underestimated disease extent. Most patients with potentially resectable disease are being treated in high-volume centres.